2020
DOI: 10.3168/jds.2020-18219
|View full text |Cite
|
Sign up to set email alerts
|

Blood perfusion of teat tissue in dairy cows: Changes associated with pre-milking stimulation and machine milking

Abstract: Mechanical forces during machine milking of dairy cows evoke circulatory impairment of the teat tissue that may affect the teats' defense mechanisms against mastitis pathogens. Ample research describes dimensional changes of different teat traits after machine milking, whereas reports that describe changes in blood circulation of dairy cows' teats are limited. Therefore, the objectives of this study were to (1) describe changes in teat blood circulation that occur after pre-milking teat stimulation and machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Changes of teat skin blood flow dependent on the milking machine settings were reported earlier also by Hamann et al (1994). More recently, Wieland et al (2020), in a study aimed to describe machine milking-induced changes in teat blood circulation of dairy cows, found that blood perfusion intensity of teats decreased after machine milking, compared with the value measured after pre-milking udder stimulation. The Authors attributed the circulatory impairment of the teat to vacuum-induced mechanical forces during machine milking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes of teat skin blood flow dependent on the milking machine settings were reported earlier also by Hamann et al (1994). More recently, Wieland et al (2020), in a study aimed to describe machine milking-induced changes in teat blood circulation of dairy cows, found that blood perfusion intensity of teats decreased after machine milking, compared with the value measured after pre-milking udder stimulation. The Authors attributed the circulatory impairment of the teat to vacuum-induced mechanical forces during machine milking.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wieland et al (2020) have studied the changes induced by machine milking in blood circulation in the teats using power Doppler sonography on 109 Holstein dairy cows. The authors observed that blood flow increased after pre-milking udder preparation, but decreased immediately after the unit detachment probably due to the mechanical stress caused by the milking machine on teat-end tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an increase in WALL% could allow for improved circulation of fluids within the teat, resulting in an overall reduction of BARREL%. Wieland et al [ 27 ] found that teat blood circulation increased after pre-milking teat stimulation and decreased after machine milking. However, the after-milking value was still higher than before stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…At the 30th minute post-milking, TCL in NC cows was signi cantly close to the pre-milking state (P < 0.01) compared to SCH cows, and there was a signi cant correlational relationship between ΔTCL30-15 and blood calcium level. This situation suggests the vacuum effect created by the milking system at the 15th minute may suppress the sphincter muscle rhythmic contractions surrounding the teat canal (Paulrud, 2005;Witzel, 1965), or the inability of muscles to perform their normal functions may be caused by acute congestion and edema in the region (Hamann et al, 1994b;Wieland et al, 2020). Therefore, it can be concluded that due to the adverse effects of the milking system, the blood calcium level could not affect the TCL at the 15th minute after milking.…”
Section: Discussionmentioning
confidence: 99%